The Falklands War and Rodolfo Fogwill's Pichi Speech: Parataxis and Postmodernism (Revista de Crítica Literaria Latinoamericana, 2011)
This work deals with Los Pychi-degos (1983), by Rodolfo Fogwill, and its counter-discursive characteristics regarding the last Argentine military dictatorship (1976-1983). The constant representation of bodies and the material aspects of the Malvinas (Falkland) War (1982) assume a dialogic nature in relation to social discourses from that era. The war is narrated from a sense-materialistic perspective. This essay argues that the physical representations, along with the predominant use of coordinated sentences (parataxis), is a discursive strategy seeking to create a realistic effect, and at the same time is a mark of postmodernism. Therefore, the representation of the war diminishes the meaning of the super-nationalist discourse and turns this novel into one of the most relevant and postmodern works in the Southern Cone during its well-known period of dictatorships.
Keywords: postmodernity; body; parataxis; dictatorship; Roberto Fogwill